DESIGN OF VECTOR-BASED DESK CALENDAR AT CV. JAYA GRAPHICS - Defitri, Lendra Citra; Sinambela, Yusnia (Kreator, 2023)
The calendar is one of the objects that can never be separated from people's lives, with the existence of a calendar the community can easily manage the time that has been planned every day as a regulator of activities to make them more precise and orderly. At this time the use of calendars has decreased, the results of a survey conducted by the authors of 50 people found 76% of people preferred the use of desk calendars compared to wall calendars. CV. Jaya Graphic usually only produces wall calendars with unattractive designs. This can be an obstacle for the company because it can result in a decrease in annual turnover. Based on the problems described above, the authors developed a desk calendar product with a vector-based image design. The advantages of vector-based images are that when the image is enlarged it will not break so that it can illustrate the advantages of the printed result with a firm shape and sharp colors